High-Throughput Transposon Mutagenesis of Corynebacterium glutamicum and Construction of a Single-Gene Disruptant Mutant Library - Suzuki, Nobuaki (American Society for Microbiology, 2006)
A simple and high-throughput transposon-mediated mutagenesis system employing two different types of transposons in combination with direct genomic DNA amplification and thermal asymmetric interlaced PCR (TAIL-PCR) was developed. Each of the two minitransposons based on IS31831 (ISL3 family) and Tn5 (IS4 family) was integrated into the Corynebacterium glutamicum R genome. By using BLAST and Perl, transposon insertion locations were automatically identified based on the sequences of TAIL-PCR products of mutant cells. Insertion locations of 18,000 mutants were analyzed, and a comprehensive insertion library covering nearly 80% of the 2,990 open reading frames of C. glutamicum R was generated. Eight thousand of the mutants, exhibiting disruption in 2,330 genes, survived on complex medium under normal laboratory conditions, indicating that the genes were not essential for cell survival. Of the 2,330 genes, 30 exhibited high similarity to essential genes of Escherichia coli or Bacillus subtilis. This approach could be useful in furthering genetic understanding of cellular life and facilitating the functional analysis of microorganisms.